2004
DOI: 10.1113/jphysiol.2004.072298
|View full text |Cite
|
Sign up to set email alerts
|

Advanced vaginal opening and precocious activation of the reproductive axis by KiSS‐1 peptide, the endogenous ligand of GPR54

Abstract: The awakening of the gonadotrophic axis at puberty is the end-point of a complex cascade of sex developmental events that leads to the attainment of reproductive capacity. Recently, loss-of-function mutations of the gene encoding GPR54, the putative receptor for the KiSS-1-derived peptide metastin, have been linked to hypogonadotrophic hypogonadism, both in rodents and humans. However, the actual role of the KiSS-1/GPR54 system in the timing of puberty onset remains unexplored. We report herein that chronic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
284
3
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(316 citation statements)
references
References 31 publications
16
284
3
13
Order By: Relevance
“…Ablation of the GPR54 (12, 13) or the Kiss1 (13, 14) gene renders mice of either sex hypogonadotropic and infertile. Kisspeptin is a powerful GnRH secretagogue (15,16), and kisspeptin administration advances puberty onset (17,18), whereas GPR54 antagonists delay puberty onset (19). These data provide compelling support for the idea that activation of kisspeptin neurons precipitates the pubertal stimulation of GnRH neurosecretion.…”
supporting
confidence: 66%
“…Ablation of the GPR54 (12, 13) or the Kiss1 (13, 14) gene renders mice of either sex hypogonadotropic and infertile. Kisspeptin is a powerful GnRH secretagogue (15,16), and kisspeptin administration advances puberty onset (17,18), whereas GPR54 antagonists delay puberty onset (19). These data provide compelling support for the idea that activation of kisspeptin neurons precipitates the pubertal stimulation of GnRH neurosecretion.…”
supporting
confidence: 66%
“…Matsui et al (2004) demonstrated that peripheral administration of kisspeptin to prepubertal, 25-day-old female rats stimulates LH secretion and induces ovulation in the rat. Shortly thereafter, Navarro et al (2004aNavarro et al ( , 2004b demonstrated a similar effect of kisspeptin on LH secretion in prepubertal male rats and showed that kisspeptins could advance the timing of vaginal opening in females. If kisspeptins trigger puberty onset, one would expect to see an increase in KiSS-1 mRNA and/or GPR54 mRNA expression during this time.…”
Section: Kisspeptin Regulation Of the Reproductive Axis 625mentioning
confidence: 99%
“…However, GnRH neurons in the preoptic area do not express LEPR-b, indicating that leptin indirectly regulates these cells by acting on interneurons upstream of GnRH neurons. In fact, GnRH cell bodies are not affected by leptin directly [31] and other neuropeptides (target for leptin), such as NPY [32,33] and kisspeptin [30,[34][35][36] and proopiomelanocortin (POMC) [35] could mediate the action of leptin. In addition to the stimulatory effect on the HPG axis at the hypothalamic level, leptin has direct effects on the anterior pituitary as well [37].…”
Section: Role Of Leptin In the Regulation Of Gonadotrophs Secretionmentioning
confidence: 99%